Green bond market-related dynamic correlations and volatility spillovers: Systematic literature review : DOI: 10.5937/etp2503047J - Jolović, Nevena; Pjanić, Miloš; Jolović, Ivana (Ekonomija - teorija i praksa, 2025)
Given the green bond universe’s expansion, grasping the evolvement of empirical investigations on green bond market-related dynamic correlations and volatility spillovers is paramount. The research aims to generate a systematic literature review considering these investigations’ evidence, delineate dominant green bond-correlated markets and volatility transmissions, ascertain prevalent econometric models employed, and unveil recurring patterns in research findings. To attain the research aim, the academic literature databases’ - Web of Science, Scopus, and Google Scholar - collections were scrutinized, and the PRISMA systematic literature review methodology’s recommended phases - identification, screening, eligibility, and inclusion - were followed. Articles’ selection criteria included the article’s content validity, relevance to the research question, evidence robustness, and recency of publication. Finally, the research was built on the latest (2019-2024 period) empirical knowledge, extracted from a total of 30 pertinent articles published in 18 reputable academic journals. The research findings documented a solid knowledge foundation and spawned recommendations valuable for both academic and non-academic actors.